Increased Blood Pressure As A Prediction Factor Of Stroke Incidence In Tulungagung District - Angga Miftakhul Nizar; Farida Farida; Anis Murniati (Jurnal Penelitian, 2022)
Stroke is a sudden neurologic disorder that occurs due to restriction or cessation of blood flow through the arterial supply system. High blood pressure causes an increase in peripheral blood pressure, causing a poor hemodynamic system and thickening of blood vessels and hypertrophy of the heart muscle. The aim of this research is to analyze the relationship between blood pressure and stroke events at the Karangrejo Health Center.The research was conducted on 10-13 November 2022. The type of research was correlation, analytic design with a cross-sectional approach and the research instrument was a questionnaire. The study population is a portion of stroke patients at the Karangrejo Health Center. Samples were taken by purposive sampling technique of 30 respondents. Blood pressure independent variable, stroke incident dependent variable. Data were analyzed with the Spearman rho test.The results showed that more than half of the respondents had blood pressure in the Severe Hypertension category, namely 13 respondents (43.3%). Most of the respondents had a history of Non-Hemorrhagic Stroke, namely 20 respondents (66.7%). Spearman Rho statistical test obtained P Value = 0.000 0.05 so that H1 is accepted, which means there is a relationship between blood pressure and stroke events at the Karangrejo Health Center, Karangrejo District, Tulungagung Regency. Blood pressure is very closely related to the incidence of stroke. This proves that it is important to control blood pressure in hypertensive patients so that they can anticipate complications of stroke.